PENGARUH MODEL PEMBELAJARAN SAVI (Somatic Auditory Visualization Intellectualy) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP NEGERI 41 PALEMBANG - Wendy Anggriani; Dina Octaria (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Abstract— The SAVI learning model is a lesson that emphasizes that learning must utilize all the sensory devices that students have. The purpose of the research is to determine whether or not the influence of learning model SAVI (Somatic Auditory Visualization Intellectually) to the mathematical communication ability of SMP Negeri 41 Palembang students. The population in this study is all students of class VII which amounted to 230. Samples taken in this study are class VII.1 which amounted to 30 students as an experimental class using SAVI (Somatic Auditory Visualization Intellectualy) and class VII.2 which amounted to 30 students as control class by using conventional learning. The design of experimental method used is Posttest-Only Control Design. Technique of collecting data using test technique. Data were analyzed by using independent sample t test, with significant level of 5%. The result of this research is there is significant influence between SAVI learning model (Somatic Auditory Visualization Intellectually) to the mathematical communication ability of students of Junior High School 41 Palembang Keywords— Somatic Auditory Visualization Intellectually, Mathematical Communication. Abstrak— Model pembelajaran SAVI adalah pembelajaran yang menekankan bahwa belajar haruslah memanfaatkan semua alat indra yang dimiliki siswa. Tujuan dari penelitian yaitu untuk mengetahui ada atau tidak pengaruh model pembelajaran SAVI (Somatic Auditory Visualization Intellectually) terhadap kemampuan komunikasi matematis siswa SMP Negeri 41 Palembang. Populasi dalam penelitian ini adalah seluruh siswa kelas VII yang berjumlah 230. Sampel yang diambil dalam penelitian ini adalah kelas VII.1 yang berjumlah 30 siswa sebagai kelas eksperimen dengan menggunakan model pembelajaran SAVI (Somatic Auditory Visualization Intellectualy) dan kelas VII.2 yang berjumlah 30 siswa sebagai kelas kontrol dengan menggunakan pembelajaran konvensional. Bentuk desain metode eksperimen yang digunakan yaitu Posttest-Only Control Design. Teknik pengumpulan data menggunakan teknik tes. Data dianalisis dengan menggunakan independen sample t test, dengan taraf signifikan 5%. Adapun hasil dari penelitian ini adalah ada pengaruh yang signifikan antara model pembelajaran SAVI (Somatic Auditory Visualization Intellectually) terhadap kemampuan komunikasi matematis siswa SMP Negeri 41 Palembang Kata Kunci— Somatic Auditory Visualization Intellectually, Komunikasi matematis.